(untitled) (TUTA Journal, 2024)
Education develops human personality, thoughts, dealing with others and prepares people for life experiences. Education is the backbone for all round development of the nation. The educational status is regarded as one of the crucial factors for assessing human development index of a country. In Nepalese context, different educational policies have been adapted in the country after almost every democratic movement, with an aim to enhance student access to quality education. Purbanchal University, has been playing leading role to provide education to the people through several different constituents as well as affiliated campuses throughout the country. However, the condition of student access to higher education in terms of their gender, ethnicity, and geographical proximity is still not satisfactory. The present study is concerned with the current scenario of student access to higher education in Purbanchal University.